Water Remediation Based on Oil Adsorption Using Nanosilicates Functionalized with a Petroleum Vacuum Residue - Camilo A. Franco; Maricelly Martínez; Pedro Benjumea; Edgar Patiño; Farid B. Cortés (Adsorption Science & Technology)
Discharging water from oilfields has become one of the major environmental issues related to the oil industry. This work presents a study on the adsorption of oil onto nanoparticles of hydrophobic silica and silica nanoparticles functionalized with a petroleum vacuum residue (VR) at 2 and 4 wt% to reduce the amount of oil in oil–brine and oil–water emulsions at different pH values (5, 7 and 9). The initial concentration of crude oil in water ranged from 500 to 1500 mg/l. The change in oil concentration after adsorption was determined using a UV–VIS spectrophotometer. Experimental data on the adsorption kinetics were fitted to pseudo-first-order and pseudo-second-order models, with better results being obtained for the latter. Results of the study showed 100% oil removal for all the systems studied and a better performance was achieved for oil-saltwater emulsions than the experiments performed using oil-saltwater emulsions. In addition, the adsorption equilibrium was achieved faster for the oil–water emulsion using the salty medium. Adsorption velocity was higher for neutral and basic systems compared with acid ones, and it was improved by increasing the amount of VR on silica surface.